An Investigation of the Usability of a Teleconsent System. (December 2020) - Ponathil, Amal; Bhanu, Aasish; Rogers, Hunter; Wilson, Mackenzie; Chalil Madathil, Kapil
Telemedicine allows providers to facilitate online medical consultation to patients when there is a geo-graphical distance between them. Similar to other medical consultations, consent is required to receive medical care. Teleconsent, developed to accommodate this requirement, allows providers to collect patient consent via screen-sharing and videoconferencing. However, its usability needs to be evaluated to improve user acceptance. This study uses a heuristic evaluation to identify the usability issues associated with a tele-consent interface. Based on Nielsen's 10 heuristics, four experts independently evaluated the consent form on two devices (desktop and smartphone), identified violations and assigned severity. Of the 70 violations identified 33.43% violated consistency and standards and 20% violated user control and freedom. Issues requiring immediate attention included the patient's inability to scroll and zoom (specific to smartphone) while navigating the consent form and the unintuitive signing process. Remediations were suggested to improve the teleconsent system usability.